Chemical Composition and Physical Characteristics of Orange Peel Essential Oil - Ikarini Imro’ah; Suwarda Rosniyati; Hanif Zainuri; Triasih Unun; Ashari Hasim (E3S Web of Conferences, 2023)
The citrus-based food and beverage industry is limited to using fruit flesh as the main raw material. Orange peels that cannot be utilized are disposed of as waste. The potential of citrus peel is very high to be processed into essential oil. Essential oils are widely used in the pharmaceutical, food, and agricultural industries. Various citrus varieties in Indonesia have different characteristics, including the content of essential oils in peel waste. The process of making essential oils can be done by distillation. This research was conducted to find out the chemical and physical of various essential oils from citrus varieties (RGL Mandarin, Gamindo B, and Montaji Agrihorti lemon). The test results show that the yield of each essential oil of RGL Mandarin, Gamindo B, and Montaji Agrihorti lemon is 3,866%; 1,174%; and 3,615%. The volatile compound content tested using GC-MS in Gamindo B citrus essential oil contained 3 compounds, RGL Mandarin found 4 compounds, and Montaji Agrihorti lemons found 4 compounds. A sensory preference test on color and odor attributes was conducted on 30 panelists. Montaji Agrihorti Lemon essential oil is the most preferred by color and Gamindo B essential oil is the most preferred by odor.